Manifestations of the world of ideas and the problematic of civilizational awareness in the Arabic Novel: A critical approach in the light of Malik Bennabi’s thought - AGGOUNE, Abire; BELHADJI, Fatiha (The International tax journal, 2026)
It appears that the movement of urban societies has its precedents and is subject to laws similar to those governing most human movements. The great miracles of history are the fusion of powerful ideologies and effective driving ideas. The world of ideas is merely a threshold that helps us better understand our situation, and this is the first step in building civilization. Speaking of the latter brings to mind the Algerian thinker Malek Bennabi, whose civilizational triad is frequently invoked. We will elaborate on it, beginning with the crisis of the idea in an era of objectification, then the distortion of consciousness between the idea and the idol, before concluding with the effectiveness of ideas as a cause of progress and development over time. In this context, literature represents a mirror to these worlds; it reflects ideas and standards, portrays characters and their experiences, and observes the material conditions and environment that shape human behavior. Thus, literature becomes a tool for understanding society and analyzing its civilizational trajectories, linking thought and human reality.